Kulturen der Gattung Poetik im Kontext, 1750 - 1950 - Michler, Werner (Wallstein Verlag, 2015)
Cultures of Genre aims at a comprehensive, systematic and historical re-evaluation of the category of literary genre in German literature 1750-1950. It investigates aspects of the historical relationship between orders of knowledge, orders of literary genre and social orderings. Based on an understanding of genre as a performative act of cultural classification, the book analyzes the cultural poetics of writers and theorists including Johann Gottfried Herder, Johann Wolfgang v. Goethe, Jacob Grimm, Karoline v. Günderrode, Bettine v. Arnim, Adalbert Stifter, Georg Lukács, Walter Benjamin, Hugo v. Hofmannsthal and Bertolt Brecht.